Natural Products and Their Derivatives with Antibacterial, Antioxidant and Anticancer Activities - Thu V. Vuong (MDPI AG, 2021)
Natural products and their derivatives have been commonly used in our daily life, as they play important roles in boosting immune systems and fighting diseases [...]